Peningkatan Kesadaran Hukum Siswa terhadap Bahaya Perilaku Bullying di MA DDI Padanglampe - Rezah, Farah Syah; Sapada, Andi Tenri; Hamza, Yuli Adha; Mangarengi, Arianty Anggraeny (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The activity of community dedication which is done at MA DDI Padanglampe to increase the legal awareness about bullying impacts by using need sssessment methods, legal counseling, accompaniment, and evaluation for the students of MA DDI Padanglampe. The purpose of this activity is to understand the dangers of bullying for the victims and perpetrators. Therefore, the activity of legal counselling and accompaniment were programmed for the students of MA DDI Padanglampe and the results were, they learned about various forms of bullying; they learned tips to avoid bullying and ready not to become part of the bullying perpetrators; and be aware of the bullying impacts.